2015
DOI: 10.4049/jimmunol.1501874
|View full text |Cite
|
Sign up to set email alerts
|

IRAK1 Drives Intestinal Inflammation by Promoting the Generation of Effector Th Cells with Optimal Gut-Homing Capacity

Abstract: IL-1R–associated kinase (IRAK) 1 is an important component of the IL-1R and TLR signaling pathways, which influence Th cell differentiation. In this study, we show that IRAK1 promotes Th17 development by mediating IL-1β–induced upregulation of IL-23R and subsequent STAT3 phosphorylation, thus enabling sustained IL-17 production. Moreover, we show that IRAK1 signaling fosters Th1 differentiation by mediating T-bet induction and counteracts regulatory T cell generation. Cotransfer experiments revealed that Irak1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Lastly and most importantly, treatment of CD8 ϩ T cells with ⌬ 9 -THC, a potent psychotropic anti-inflammatory cannabinoid in marijuana, effectively prevented CD8 ϩ T-cell activation and proliferation, miR-150 downregulation, and IRAK1 protein upregulation. Collectively, elevated IRAK1 protein expression in response to miR-150 downregulation may greatly facilitate the downstream transduction of proinflammatory signals, thus creating a persistent inflammatory environment in the intestine, as demonstrated recently using an IRAK1 knockout mouse model (51). In addition, our findings also suggest that cannabinoids provide a feasible strategy to decrease persistent immune activation/inflammation in HIV/ SIV infection.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Lastly and most importantly, treatment of CD8 ϩ T cells with ⌬ 9 -THC, a potent psychotropic anti-inflammatory cannabinoid in marijuana, effectively prevented CD8 ϩ T-cell activation and proliferation, miR-150 downregulation, and IRAK1 protein upregulation. Collectively, elevated IRAK1 protein expression in response to miR-150 downregulation may greatly facilitate the downstream transduction of proinflammatory signals, thus creating a persistent inflammatory environment in the intestine, as demonstrated recently using an IRAK1 knockout mouse model (51). In addition, our findings also suggest that cannabinoids provide a feasible strategy to decrease persistent immune activation/inflammation in HIV/ SIV infection.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, mice lacking IRAK1 fail to mount an inflammatory response and produce significantly lower levels of proinflammatory cytokines, suggesting their critical requirement for activation of the NF-B signaling pathway and the subsequent inflammatory response (23). Finally, recent studies have confirmed the central role of IRAK1 in driving intestinal inflammation (50,51). Consistent with miR-150 downregulation, IRAK1 protein expression significantly increased in colonic LPLs of chronically SIV-infected macaques.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, it is possible that the interaction of nsp11 and IRAK1 triggers IRAK1 downstream activation to induce IL-17 production. It has been reported that IL-17 expression is reduced in IRAK-1 Ϫ/Ϫ mice, and these mice are protected from developing various inflammatory diseases (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between A2M and IL‐17 in AR subjects might be due to the interactions among STAT3, A2M and IL‐17. STAT3 phosphorylation might activate A2M , thus enabling sustained IL‐17 production . Probably, IL‐17A might stimulate STAT3‐A2M axis through activating JAK2 and ERK1/2 .…”
Section: Discussionmentioning
confidence: 99%